KINERJA PETUGAS PENGANGKUT SAMPAH DI KELURAHAN SAMBONGJAYA KECAMATAN MANGKUBUMI KOTA TASIKMALAYA - Deni Sudrajat (JRPA - Journal of Regional Public Administration, 2018)
This study aims to analyze the performance of garbage transportation in Sambongjaya Village, Mangkubumi Sub-district, Tasikmalaya City, using descriptive method of qualitative approach. Informants in this research are Head of Sambongjaya urban village, garbage transport officer and community in Sambongjaya village, Mangkubumi sub-district, Tasikmalaya city. The types of data in this study include primary data and secondary data, while data collection techniques conducted through in-depth interviews with informants who have information related to research studies. Research aids using interview guides, observation guides and recorders for further in-depth analysis. Based on the results of research implementation of garbage transport by officers for Sambongjaya Village Sub District Mangkubumi Tasikmalaya City still not optimal. Other problems found are related to the lack of garbage collector with lack of supporting facilities and other infrastructure, so that the garbage is piled up because it is not transported or can not be transported routinely by the garbage collector.